A FRET-based ratiometric two-photon fluorescent probe for superoxide anion detection and imaging in living cells and tissues. Issue 5 (18th January 2019) - Yao, Shan; Ma, Chunli; Lu, Yanbing; Wei, Xianzhe; Feng, Xiaowen; Miao, Pei; Yang, Guangxin; Zhang, Jing; Yan, Mei; Yu, Jinghua
Abstract : A FRET-based ratiometric two-photon fluorescent probe for superoxide anion detection and imaging in cells and tissue was reported with dual-channels. Abstract : The superoxide anion (O2 ˙ − ) plays a crucial role in several physiological processes and many human diseases. Developing new methods for O2 ˙ − detection in biological systems is very important. A FRET-based two-photon (TP) fluorescent probe with a ratiometric signal, TFR-O, was developed. A naphthalene derivative based TP fluorescent group was selected as the energy donor group, and a rhodol fluorescent group was chosen as the energy acceptor; the trifluoromethanesulfonate group was chosen as the recognition moiety. After reacting with O2 ˙ −, the recognition moiety was removed and the fluorophore was released, leading to a fluorescence intensity decrease at the wavelength of 425 nm and a significant enhancement of the fluorescence intensity at 550 nm. The fluorescence intensity ratio between 550 and 425 nm ( I 550 / I 425 ) varied from 0.15 to 6.72, with the O2 ˙ − concentration increasing from 0 to 50 μM. The detection limit of theTFR-O was 83 nM. Moreover, TFR-O was applied for detecting and imaging O2 ˙ − in cells and liver tissues.